Does A Family Size Have an Effect on Empathy Level? : Filling the Gap in Empathy Literature - Promsri, Dr. Chaiyaset (Academy of Social Science Journal, 2019)
The purpose of this study was to scrutinize the effect of a number of family members on empathy level. A sample of 67 students in 2-year program in accounting who registered in strategic management course was gathered for data collection. An adjusted version of the Toronto Empathy Questionnaire was employed to assess empathy level among students. Findings indicated that the average number of students’ family members was 4-5 people. The empathy level of students was reported at a high level (M = 2.85, S.D. = .345). Analysis of linear regression analysis designated that a number of family members could explain 7.1% of variance to empathy level among this group of students. Results also found that a number of family members significantly predicted students’ empathy level (ß = .266, p <.05). In conclusion, the more family members a student had, the more empathetic he/she was